2010
DOI: 10.1007/s13197-010-0160-8
|View full text |Cite
|
Sign up to set email alerts
|

Physico−chemical, respiratory and fungicide residue changes in wax coated mandarin fruit stored at chilling temperature with intermittent warming

Abstract: Influence of chilling temperature, intermittent warming (IW) and fungicidal wax coating was evaluated during storage of 'Nagpur' mandarins (Citrus reticulata Blanco). Fruits were light green coloured with slight colour-break at the start of storage. Waxed and non-waxed fruits were stored at 3.5°C (constant), 2 weeks at 3.5°C followed by IW for 1 week at 19.5°C (cycle) and at 6.5°C (constant), and were evaluated immediately after 30, 45, 60, 75 days and also after 1 week holding at ambient condition (24±2°C, 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 22 publications
(9 reference statements)
5
18
0
2
Order By: Relevance
“…Similarly, Özdemir et al (2016) reported that fruit from the Fremont mandarin cultivar grafted on Carrizo citrange had higher juice content than fruit grafted on sour orange during storage. The decrease in juice content during storage was reported in previous studies on mandarin (Pekmezci, 1984;Kaşka, 1992, 1994;Gül, 1996;Pekmezci et al, 1997;Agabbio et al, 1999;Ragone, 1999;Şen, 2004;Şen and Karaçalı, 2005;Özdemir et al, 2005, 2007, 2008Özkaya, 2007;Ladaniya, 2011). Similarly, Gürgen et al (1995) reported that the highest juice content occurred in fruit from the Marsh Seedless grapefruit cultivar grafted on Troyer citrange during storage.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Similarly, Özdemir et al (2016) reported that fruit from the Fremont mandarin cultivar grafted on Carrizo citrange had higher juice content than fruit grafted on sour orange during storage. The decrease in juice content during storage was reported in previous studies on mandarin (Pekmezci, 1984;Kaşka, 1992, 1994;Gül, 1996;Pekmezci et al, 1997;Agabbio et al, 1999;Ragone, 1999;Şen, 2004;Şen and Karaçalı, 2005;Özdemir et al, 2005, 2007, 2008Özkaya, 2007;Ladaniya, 2011). Similarly, Gürgen et al (1995) reported that the highest juice content occurred in fruit from the Marsh Seedless grapefruit cultivar grafted on Troyer citrange during storage.…”
Section: Discussionsupporting
confidence: 67%
“…Hydrolysis of cell wall constituents could also possibly contribute to the increase in degrees Brix (Burns, 1990). It has been reported in previous studies that the TSS content of mandarins decreased during storage (Pekmezci, 1984;Kaşka, 1992, 1994;Gül, 1996;Pekmezci et al, 1997;Ragone, 1999;Şen, 2004;Şen and Karaçalı, 2005;Salvador et al, 2006;Özdemir et al, 2005, 2007, 2008Özkaya, 2007;Ladaniya, 2011;Karaşahin et al, 2014). Unlike our findings, Obenland et al (2011) reported that TSS content increased during 7 weeks of storage in Owari and W. Murcott mandarins.…”
Section: Discussionmentioning
confidence: 93%
“…This was probably due to less concentration of juice because of low transpiration because coating with coconut oil sealed the opening of pore/stomata and controlled the dehydration process of fruits (Kulkarni et al, 2010). Initial value of ascorbic acid, total sugar and reducing sugar of Nagpur mandarin was 30.8 mg 100 ml -1 , 8.1% and 3.7%, respectively found by Ladaniya (2011). In this study total sugar and reducing sugar of mandarin was 10.78% and 4.17%, respectively at initial stage, but these values were increased slightly with storage period.…”
Section: Ascorbic Acid Sugar (Total Reducing) Ph and Tss Contentmentioning
confidence: 87%
“…To prevent these adverse effects, use of environmentally friendly technologies such as edible coating or salicylic acid are of prime important (Saucedo et al, 2007Ladaniya, 2011. Salicylic acid exhibits a high potential in enhancing quality, controlling post-harvest losses and mitigating chilling injury in fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%